2013
DOI: 10.4269/ajtmh.12-0560
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Anemia among Preschool Children in Rural, Western Kenya

Abstract: Although anemia in preschool children is most often attributed to iron deficiency, other nutritional, infectious, and genetic contributors are rarely concurrently measured. In a population-based, cross-sectional survey of 858 children 6–35 months of age in western Kenya, we measured hemoglobin, malaria, inflammation, sickle cell, α-thalassemia, iron deficiency, vitamin A deficiency, anthropometry, and socio-demographic characteristics. Anemia (Hb < 11 g/dL) and severe anemia (Hb < 7 g/dL) prevalence ratios (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
86
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 41 publications
24
86
1
7
Order By: Relevance
“…It was also consistent with the finding that stunted children were 2.7 times more likely to be anemic than their counterpart [10]. This finding also agreed with other studies conducted in Bangladesh [23], Brazil [24], Burma [25] and Kenya [26]. Moreover, the likelihood of being anemic was high in wasted children.…”
Section: Discussionsupporting
confidence: 91%
“…It was also consistent with the finding that stunted children were 2.7 times more likely to be anemic than their counterpart [10]. This finding also agreed with other studies conducted in Bangladesh [23], Brazil [24], Burma [25] and Kenya [26]. Moreover, the likelihood of being anemic was high in wasted children.…”
Section: Discussionsupporting
confidence: 91%
“…26 Studies in Zanzibar, similarly, found no association between helminth infection early in life and anemia or malnutrition, which is hypothesized to be secondary to increased environmental exploration and thus, increased exposure to STH by better-nourished children. 27 However, in a 12-month deworming trial of children 6-71 months of age, mebendazole improved anemia only in children 24 months of age, suggesting that young children may still benefit from deworming, because they are at higher risk of anemia, although at lower intensity of helminth infection.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study in Kenya, researchers found that while malaria was the leading factor associated with anemia, iron deficiency, inflammation, blood disorders, and stunting were also associated with anemia among children under 5 years. 6 As such, interventions aimed at anemia prevention and treatment must be targeted to be optimally effective. Although the UMIS did not collect data on nutritional deficiencies, multiple previous studies have documented the high percentage of anemia attributed to iron deficiency globally.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although it is estimated that nearly half of all cases of anemia are due to iron deficiency, the other causes of anemia, which also disproportionately affect children and pregnant women, are multifactorial and include nutritional deficiencies and parasitic infections. [4][5][6][7][8] Iron deficiency anemia (IDA) in children is particularly detrimental as it can stunt development because additional iron is necessary during growth. The role of IDA in cognitive impairment and psychomotor development is also well recognized.…”
Section: Introductionmentioning
confidence: 99%